In vitro immune responses of bovine mammary epithelial cells induced by Escherichia coli, with multidrug resistant extended-spectrum β-lactamase, isolated from mastitic milk. (December 2020) - Zhuang, Cuicui; Huo, Wenlin; Liu, Gang; Shahid, Muhammad; Gao, Jian; Barkema, Herman W.; Rahman, Sadeeq ur; Kastelic, John P.; Han, Bo
Abstract: Bovine mastitis is an inflammatory condition of mammary glands causing huge economic losses for dairy industries. Infection with extended-spectrum β-lactamase (ESBL)-producing sequence types (ST) 410- Escherichia coli (ESBL-ST410 E. coli ) is considered a leading cause of bovine mastitis in China. However, pathogenic effects of these strains in an in vitro model, e.g. bovine mammary epithelial cells (bMECs), are unknown. Therefore, our objectives were to explore pathogenesis (adhesion and invasion, inflammation, oxidative stress and apoptosis) of ESBL- E. coli (highly prevalent in bovine mastitis) in bMECs. Non-pathogenic E. coli DH5α and a prototypical E. coli P4 were included as negative and positive controls, respectively. The bMECs were infected with our isolated ST410 strains, plus DH5α and P4, with assessment of the following end points: adhesive and invasive capabilities; lactate dehydrogenase (LDH) activities; inflammatory responses, including concentrations of interleukin-1β (IL-1β), IL-6, IL-10 and tumor necrosis factor-α; oxidative stress including intracellular reactive oxygen species production, malondialdehyde concentrations, activities of glutathione peroxidase and superoxide dismutase; and apoptosis. All ST410 strains had greater adhesive and invasive capabilities and increased LDH release, with varying degrees of inflammatory responses, oxidative stress and apoptosis compared to blank and DH5α groups, similar to P4-infected bMECs. In particular, ST410(4) was more likely than the other 3 isolates to adhere to and invade bMECs and increase LDH activities, cytokine release, oxidative stress and apoptosis. Thus, ST410 isolates had pathogenic manifestations of adhesive and invasive capabilities; furthermore, they induced inflammation, oxidative stress and apoptosis in bMECs. Finally, ST410(4) was the most pathogenic strain. Graphical abstract: Image 1 Highlights: Extended-spectrum β-lactamase -producing sequence types 410- Escherichia coli clinical isolates adhered to and invaded bMECs. All ESBL-ST410 E. coli induced inflammation, oxidative stress and apoptosis in bMECs. Adhesive, invasive and pathogenic capabilities of ST410(4) markedly contributed in inflammation, oxidation and apoptosis.